Educational Mobile Robot Programmed by Microcontroller - Paul Ciprian PATIC; Gabriela MĂNTESCU (Communications of International Proceedings, 2021)
One aspects in the human’s evolution is the use of tools that simplify the physical work. Robots also fall into this category, but they have a stong engineering position due to their complexity. Humans imagined intelligent robots that would take over a significant part of the physical effort. Thus its has built automatic devices and intelligent mechanisms or different robots, nowadays many robotic systems are around us, being everywhere. A robot is a mechanical or virtual/artificial operator. Most robots are used in manufacturing processes. Others can be used as remote-controlled manipulators. Some robots are mobile, with a built-in locomotion system, being able to move on land, on water, in the air. The modes of propulsion are among the most diverse, such as on wheels, water, water jet or air etc. In this paper, one tried to present an educational mobile robot, imposing a rather complex wiring diagram, a command and control of the robot made by a PIC16F84A microcontroller. This robot can be used in teaching and educational activities, but also in surveillance tasks, monitoring of spaces difficult for humans to penetrate, harmful areas.
Keywords: Driving System; Mobile Robot; Microcontroller; Programming Controller; Sensor System; Simulation Program